Performance Evaluation of Evacuated Tube Solar Collector Using Water-Based Titanium Oxide (TiO2) Nanofluid - Mahendran, Moorthy; Lee, Giok Chui; Sharma, K. V.; Shahrani, Anuar (Faculty Mechanical Engineering, UMP, 2012)
Experiments are undertaken to determine the efficiency of evacuated tube solar collector using water-based Titanium Oxide (TiO2) nanofluid at Pekan campus (3˚32’ N, 103˚25’ E) Faculty of Mechanical Engineering, University Malaysia Pahang for conversion of solar thermal energy. Malaysia lies in the equatorial zone with an average daily solar insolation of more than 900 W/m² and can reach a maximum of 1200 W/m² for most of the year. Traditionally, water is pumped through the collector at an optimum flow rate, for extraction of solar thermal energy. If the outlet temperature of water is high, further circulation of water through the collector is useless. This is due to low thermal conductivity of water of 0.6 W/m.K compared to metals which is many orders higher. Hence, it is necessary to reduce the surface temperature either by pumping water at higher flow rate or by enhancing the fluid properties by dispersing with nanoparticles. Pumping water at higher flow rates is not advantageous as the overall efficiency of the system is lowered. Liquids in which nanosize particles of metal or their oxides are dispersed in a base liquid such as water are known as 'Nanofluid'. It results in higher values of thermal conductivity compared to the base liquid. The thermal conductivity increases with concentration and temperature of the nanofluid. The increase in thermal conductivity with temperature is advantageous for applications in collectors, as the solar insolation varies throughout the day, with a minimum in the morning reaching a maximum at 2.00p.m and reducing thereafter. The efficiency of the collector estimated using TiO2 nanofluid of 0.3% concentration is about 0.73, compared to water which is about 0.58. The efficiency is enhanced by 16.7% maximum with 30-50nm size TiO2 nanoparticles dispersed in water, compared to the system working with water. The flow rate is fixed at 2.7 litres per minute for both liquids.